Biotransformation of Geniposide into Genipin by Immobilized Trichoderma reesei and Conformational Study of Genipin. (12th April 2018) - Yang, Yishun; Ding, Yue; Zhang, Tong
Abstract : Trichoderma reesei QM9414, Trichoderma viride 3.316, Aspergillus niger M85, and Aspergillus niger M92 were screened for hydrolyzing geniposide into genipin. T. reesei was selected according to the β -glucosidase activity of the fermentation broths using geniposide as a substrate. T. reesei was immobilized by embedding method using sodium alginate as the carrier. Geniposide was hydrolyzed by immobilized T. reesei at 28°C (200 rpm) for 34 h, and the yield of genipin was 89%. The product was purified and identified by UV, IR, EIMS, and 1 H-NMR. Since there were two sets of signals in 1 H-NMR spectra, a series of experiments were performed and verified that the existence of two conformations was the main reason. Generally, biotransformation of geniposide into genipin by immobilized T. reesei provides a promising solution to the genipin production.